Impact of active pulmonary tuberculosis on the prognosis of patients with upper aerodigestive cancers: An 8-year observational study in a nationwide cohort - Chung-Lin Hung; Chien-Chou Su; Chih-Ying Ou (Elsevier, 2022)
Background and objective: Tuberculosis (TB), a contagious disease with high morbidity and mortality, is prevalent among immunocompromised patients including those with cancers. We describe the risk subgroups and impact of active TB on the prognosis of patients with upper aerodigestive cancers. Methods: We conducted a retrospective, nationwide cohort study from January 2009 to December 2014, and followed up until the end of 2016, using the database of the Taiwanese National Health Insurance (NHI) program. Patients newly diagnosed with oral, nasopharyngeal, laryngeal, and esophageal cancers were defined as the upper aerodigestive cancer cohort. Active pulmonary TB infection was identified as a time-dependent variable in the analysis of the risk subgroups and prognostic impact in our study cohort. Results: A total of 57,543 patients were enrolled, and 890 patients (1.55 %) had active pulmonary TB during the follow-up period. The TB incidence was highest in patients with esophageal cancer and lowest in patients with nasopharyngeal cancer (1443 and 236 per 100, 000 person-years, respectively). Moreover, advanced cancer stage and inoperable cancer are considered risk factors for TB. Furthermore, patients with TB infection had a shorter survival (HR: 1.86, 95 % CI: 1.70-2.04), after matching cancer type, stage, and calendar year of diagnosis with patients without TB. Conclusion: Active pulmonary TB is prevalent in patients with upper aerodigestive cancers and is independently associated with an increased risk of death. Identifying the risk factors for TB in these cancer patients is important both for infectious disease control and outcome evaluation.